Does the Harvesting Site Influence the Osteogenic Potential of Mesenchymal Stem Cells? - Van Thi Nguyen; Irene Tessaro; Antonio Marmotti; Camilla Sirtori; Giuseppe M. Peretti; Laura Mangiavini (Stem Cells International)
Total hip arthroplasty (THA) represents one of the commonest surgical procedures in the orthopedic field. Osteointegration of the implant with native bone is essential for an optimal result; thus, the quality of the patient’s bone surrounding the implant (i.e., the bone stock) is crucial. However, in some cases, the bone stock is insufficient and needs to be improved with autologous grafts rich in multipotent cells (i.e., from the iliac crest, from the head of the femur, or from the subchondral bone harvested from the acetabulum) or allogenic frozen bone. It is not known if the harvesting site may influence the osteogenic potential of these cells. Thus, our aim was to characterize and compare multipotent cells collected from the bone marrow, acetabular subchondral bone, and trabecular bone on the femoral head with a focus on osteogenic differentiation. The cells from three sources had a fibroblast-like phenotype and expressed surface antigens CD73, CD90, and CD105 and are negative to CD11b, CD34, and CD45. Although all these cells could be induced to differentiate into osteoblasts, chondrocytes, and adipocytes, they displayed different differentiation potentials. In osteogenic differentiation condition, the cells from the acetabulum had the lowest accumulation of calcium deposit while the cells originated from the bone marrow and femur created a considerably increased amount of the deposit. These findings were confirmed by quantitative polymerase chain reaction (qPCR). In chondrogenic and adipogenic conditions, bone marrow cells possessed a predominant differential capacity compared with the others, illustrated by high collagen type II expression together with a cartilage-like lacuna structure and the presence of fat-specific markers, respectively. To our knowledge, this is the first study comparing and demonstrating that the progenitor cells obtained from diverse surgical sites in hip replacement procedure share common characteristics of MSC but differ about plasticity and may provide rational for clinical application in cell therapy and bone grafting. The project number L1033 is registered with ClinicalTrials.gov NCT03369457.